2013
DOI: 10.1007/s11684-013-0296-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of prophylactic transpapillary pancreatic stenting in distal pancreatectomy: a meta-analysis

Abstract: Pancreatic fistula (PF) is the most frequent complication after distal pancreatectomy (DP). Prophylactic transpapillary pancreatic stenting (PTPS) has been proposed recently for the prevention of PF after DP. In this meta-analysis, a comprehensive search was performed in the PubMed, Embase, and Cochrane Library databases. Studies analyzing the results of PTPS in DP were considered eligible for this meta-analysis. The analyzed outcome variables included PF rate, postoperative morbidity, non-PF-related complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Thus, it was hypothesized that preoperative pancreatic stenting prevents POPF after DP. A meta-analysis, including one RCT and three case-control studies, concluded that pancreatic stents in DP were associated with less POPF formation [77]. Abe et al [78] performed preoperative endoscopic pancreatic stenting for 10 patients who underwent DP, and no patients developed POPF.…”
Section: Pancreatic Stentingmentioning
confidence: 99%
“…Thus, it was hypothesized that preoperative pancreatic stenting prevents POPF after DP. A meta-analysis, including one RCT and three case-control studies, concluded that pancreatic stents in DP were associated with less POPF formation [77]. Abe et al [78] performed preoperative endoscopic pancreatic stenting for 10 patients who underwent DP, and no patients developed POPF.…”
Section: Pancreatic Stentingmentioning
confidence: 99%
“…Several studies have shown successful prophylaxis of POPF after DP by preoperative pancreatic duct stenting, which indicates that improved drainage through the papilla of Vater seems to prevent pressure-induced leakage from the pancreatic stump. 2,[12][13][14][15] This may play a pivotal role in POPF formation after DP. Although prophylactic preoperative pancreatic duct stenting is theoretically useful for preventing POPF after DP, this procedure is not recommended at present because of a lack of evidence from well-designed trials and the risk of endoscopic retrograde cholangiopancreatography (ERCP)-related complications, such as pancreatitis, cholangitis, or bleeding.…”
mentioning
confidence: 99%
“…Numerous techniques have been described to reduce the development of clinically relative POPF such as the use prophylactic pancreatic duct stenting, administration somatostatin analogues, performing a pancreatic-enteric anastomosis and the use of various electrosurgical transection methods. [20][21][22] The use of prophylactic pancreatic stenting may reduce leak rates in certain circumstances, but routine use has its own risks and cannot be advocated in all cases 23 It may be particularly be useful if there is the presence of a proximal benign proximal pancreatic duct stricture or in the setting of papillary stenosis We did not administer any somatostatin analogues in our series, although it may have a role in some circumstances. Most of the data on somatostatin analogues is however in the setting of pancreaticoduodenectomy and its potential benefits are offset against product costs.…”
Section: Discussionmentioning
confidence: 97%